Co-eruptive subsidence and post-eruptive uplift associated with the 2011–2012 eruption of Puyehue-Cordón Caulle, Chile, revealed by DInSAR - Euillades, Pablo Andrés (2017)
The 2011–2012 eruption of the Puyehue-Cordón Caulle volcanic complex, southern Andes (Chile), was associated with complex surface deformation affecting an area of roughly 50 by 50 km. We report here differential SAR interferometry (DInSAR) results of pre-, co- and post-eruptive deformation from ENVISAT ASAR, COSMO-Skymed, and ALOS-2/PALSAR scenes acquired between early 2011 and early 2017. No clear pre-eruptive deformation is observed during five months before the eruption, although some patterns could be interpreted as showing inflation occurring between April and May 2011. Co-eruptive interferograms show a complex deformation pattern consisting in a major deflation lobe (120 cm LOS lengthening) centered 10 km NW of the eruption vent accompanied by smaller uplift and subsidence regions in the vicinity of the vent. Re-inflation began immediately after the end of the eruption. A first pulse lasted 3 years between 2012 and 2015, accumulating ~ 70 cm uplift. We detect here a second pulse, beginning in June 2016 and still ongoing in February 2017, reaching 12 cm in half a year. Inverse modeling with spherical cavity and spheroidal sources locates re-inflation sources at a depth ranging between 8 and 11 km under the surface. It suggests re-filling of the reservoir occurring after the draining of a shallow magma chamber during the 2011–2012 eruption.